2023
DOI: 10.1039/d2nr06317d
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable lanthanide-doped CsPbI3 perovskite nanocrystals with near-unity quantum yield for efficient red light-emitting diodes

Abstract: CsPbI3 perovskite nanocrystals (NCs) are rising as promising photoactive materials for optoelectronic devices. However, the poor phase stability of CsPbI3 NCs has set substantial limitations in their practical application. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Great progress in terms of increasing the luminescence efficiency, stability, and operational characteristics of optoelectronic devices based on CsPbI 3 perovskite nanocrystals was achieved by introduction of Sr 2+ , [9,10] Ni 2+ , [11] Ca 2+ , [12] and Zn 2+ [13] cations. Besides, similar results were achieved through employing heterovalent doping of CsPbI 3 perovskite nanocrystals with smaller Sb 3+ , [14] Yb 3+ , [15] Gd 3+ , [16] or La 3+ [17] cations. At the same time, the B-site doping perovskites with optically active ions such as Mn 2+ , [18,19] Yb 3+ , [20,21] Er 3+ , [22,23] etc.…”
Section: Introductionsupporting
confidence: 63%
“…Great progress in terms of increasing the luminescence efficiency, stability, and operational characteristics of optoelectronic devices based on CsPbI 3 perovskite nanocrystals was achieved by introduction of Sr 2+ , [9,10] Ni 2+ , [11] Ca 2+ , [12] and Zn 2+ [13] cations. Besides, similar results were achieved through employing heterovalent doping of CsPbI 3 perovskite nanocrystals with smaller Sb 3+ , [14] Yb 3+ , [15] Gd 3+ , [16] or La 3+ [17] cations. At the same time, the B-site doping perovskites with optically active ions such as Mn 2+ , [18,19] Yb 3+ , [20,21] Er 3+ , [22,23] etc.…”
Section: Introductionsupporting
confidence: 63%
“…The corresponding normalized PL and absorption spectra of YCl3:CsPbI3 NRs showed that peak position exhibited a blue-shift owing to partial substitution of Y 3+ cation [26]. The enlarged bandgap caused the blue-shifts of the absorption and PL spectra for YCl3:CsPbI3 NRs due to the partial substitution of Pb 2+ cation and I − with bigger radius by the smaller Y 3+ and Cl − ions [27]. The photoluminescence quantum yield (PLQY) increased from 51% to 70% for the 0.184 mmol YCl3 passivated CsPbI3 NCs, suggesting enhanced radiative recombination followed by yttrium chloride doping (Figure 4c).…”
Section: Resultsmentioning
confidence: 98%
“…It is found that the EL spectra for pristine and DDAB‐incorporated PeLEDs slightly shift to higher wavelengths with respect to their PL peaks of 685, 670, 652, and 634 nm, respectively, due to the quantum‐limited Stark effect as reported previously. [ 47 ] The device current density−voltage ( J − V ) curves in Figure 4d show smaller current densities for DDAB‐incorporated PeLEDs than pristine PeLEDs, benefitting from the compact film morphology for suppressed leakage current. Meanwhile, it is found that DDAB‐incorporated PeLEDs have higher brightness than pristine devices at the same current density (below 20 mA cm −2 ) (Figure 4e), indicating that the incorporation of DDAB promotes more efficient radiative recombination.…”
Section: Resultsmentioning
confidence: 99%